Impact of dual active ingredients long-lasting insecticidal nets on the genetic structure of insecticide resistant populations of Anopheles gambiae in Southern Benin - Boulais Yovogan; Armel Djènontin; Martin C. Akogbéto; Arthur Sovi; Constantin J. Adoha; Arsène Fassinou; Albert S. Salako; Esdras M. Odjo; Landry Assongba; Manfred Accrombessi; Edouard Dangbénon; Bénoît S. Assogba; et al. (Malaria Journal)
Abstract Background Insecticide resistance amongst vector populations is a major challenge, exacerbated by the continued use of the same active ingredients. The present study assessed the impact of long-lasting insecticidal nets (LLINs) bi-treated with chlorfenapyr-alphacypermethrin (PY-CFP LLIN) or pyriproxyfen-alphacypermethrin (PY-PPF LLIN) on the genetic structure of resistant populations of Anopheles gambiae in 60 clusters divided into three arms from three districts in southern Benin. Methods The study was conducted between September 2019 and October 2021 in 123 villages grouped in 60 clusters. Mosquitoes were collected indoors and outdoors using human landing catches (HLCs) in 4 households in each cluster every 3 months. After morphological identification, a subsample of An. gambiae sensu lato (s.l.) was analysed by PCR to detect the molecular species and the presence of L1014F vgsc-kdr and G119S-ace-1 mutations. Results Anopheles coluzzii (56.9%) and An. gambiae sensu stricto (s.s.) (42.8%), with a few hybrids (0.2%), were identified within 4242 samples of An. gambiae tested. The frequency of L1014F vgsc-kdr decreased in An. coluzzii collected both indoors and outdoors locations in the PY-CFP LLIN and PY-PPF LLIN arms post-intervention compared to baseline. In An. gambiae, the frequency of the L1014F allele decreased in year one but increased above baseline in year 2. In both species, the allelic frequency of G119S-ace-1 was < 10%. For L1014F vgsc-kdr, the fixation index was positive (F IS  > 0) in both species. However, it was negative (F IS  < 0) for the presence of G119S-ace-1. Weak genetic differentiation, especially in the PY-PPF LLIN and PY-CFP LLIN arms (F ST  ≤ 0.05), was observed in An. gambiae s.s. populations with L1014F vgsc-kdr, while it was generally higher for both species with G119S-ace-1. Conclusion The frequency of the L1014F vgsc-kdr resistance allele was high, while that of the G119S-ace-1 allele was low throughout the study period. Consistent changes in allele frequencies were not observed in any of the treatment arms suggesting that the pyrethroid component of dual AI (active ingredients) nets continues to select for the resistant allele and there is little if any evidence that the non-pyrethroid insecticide selects for the wild-type kdr allele.